Linguistic and Stylistic Features of Proverbs About “Mind” - Sadagat Hasanova (CV. Rustam, 2026)
Proverbs are paremiological units that express a people’s worldview, life experience, and moral values in a concise yet profound manner. Among these, proverbs devoted to the concept of “mind” occupy a special place. These proverbs reflect generalized conclusions about human cognitive activity, thinking patterns, behavioral models, and social positions. Proverbs representing the notion of “mind” hold a central position in the paremiological systems of many languages. By expressing collective wisdom briefly and compactly, they encode cultural attitudes toward intellect, reasoning, consciousness, memory, and judgment. This article examines proverbs on the theme of “mind” in terms of their semantic, lexical, syntactic, stylistic, pragmatic, and cognitive aspects. The study demonstrates that proverbs on the “mind” are not only moral and educational tools but also linguistically rich structures that reveal how societies conceptualize human cognition. The article analyzes the lexical, semantic, syntactic, and stylistic features of proverbs about “mind,” exploring their expressive potential and communicative functions.